(untitled) - Briggs, Leslie J. (Englewood Cliffs, N.J., 1981)
This book is intended for teachers, curriculum specialists, trainers, administrators, and those who wish to become professional designers of instructional materials and programs.
Keywords: Instructional systems,Hệ thống giảng dạy; Design and construction,Thiết kế và xây dựng